Vasculitic neuropathy: Comparison of clinical predictors with histopathological outcome. Issue 6 (23rd February 2019) - Nathani, Dev; Barnett, Michael H.; Spies, Judith; Pollard, John; Wang, Min‐Xia; Kiernan, Matthew C.
ABSTRACT: Introduction :To improve diagnostic accuracy, in this study we compared prebiopsy clinical parameters with subsequent pathological confirmation of peripheral nerve vasculitis. Methods : Clinical, laboratory, and neurophysiological parameters were analyzed for consecutive patients referred for nerve biopsy with suspected vasculitis. Patients were assigned pathological categories of definite, probable, possible, or absent vasculitis using validated guidelines. Patients with definite or probable vasculitis were considered to have pathologically confirmed vasculitis. Results : From a cohort of 78 patients, biopsy confirmed vasculitis in 29.5%. Parameters that best differentiated between pathologically confirmed and pathologically unlikely vasculitis were stepwise clinical progression (34.8% vs. 5.6%), the presence of serum anti‐myeloperoxidase antibody (28.6% vs. 2.2%) and rheumatoid factor seropositivity (38.1% vs. 10.7%). Pathologically absent vasculitis was frequent in patients with normal (100%) or primarily demyelinating (87.5%) nerve conduction studies. Discussion : Factoring the negative predictors of pathologically confirmed vasculitis into decision‐making can reduce the frequency of diagnostically unhelpful nerve biopsies. Muscle Nerve 59:643–649, 2019 Abstract : See editorial on pages 635–637 in this issue .